The effects of different loading doses of dexmedetomidine on sedation - Jae Hwan Sim (Korean Journal of Anesthesiology, 2014)
BackgroundDexmedetomidine is a useful sedative drug with various uses. We designed this study to investigate the clinical effects and complications of different loading doses, 0.5 and 1.0 µg/kg.MethodsForty six patients, of American Society of Anesthesiologists physical status I and II, who required elective and emergency operation under spinal anesthesia were randomly assigned to group L or group H. Group L received a loading dose of 0.5 µg/kg for 10 minutes while group H received 1.0 µg/kg. Bispectral index (BIS), systolic blood pressure, heart rate, and Ramsay score were recorded at T0 (before loading), TL (just after loading) and T10, 20, 30 (10, 20, 30 minutes after TL). Complications, drug use, lowest BIS and time to reach BIS 80 after termination of dexmedetomidine were recorded during this study.ResultsIn group H, BIS value decreased significantly after TL compared to the baseline (T0), while in group L after T10. Between two groups, BIS values showed a significant differences only at T10, BIS of group H was lower than that of group L. Ramsay score showed no significant differences except in TL; the score of group L was significantly lower than that of group H. Other vital signs and complications showed a minimal differences between two groups.ConclusionsHigher loading dose (1.0 µg/kg) of dexmedetomidine can lead to faster sedation without any severe complications.